Empirical analysis of regional economic performance in Russia: Human capital perspective - Vadim Kufenko (Universität Hohenheim, 2012)
Having shown the important role of the Russian economy in the ex-USSR region by causality tests, we proceed to empirical analysis of growth and performance of the Russian regions. A dynamic panel data approach enabled us to obtain elasticity coefficients on proxies for convergence, physical capital, labour and innovation. After including human capital in the reformulated model we resolve endogeneity and reverse causality by introducing two instrumental variable approaches. Taking advantage of the Unified State Exam data we managed to successfully endogenize human capital by number (and share) of outperforming students and by the education index. The second approach helped to improve causality between instruments and human capital: the dates of first university foundation and distance to Moscow successfully explains human capital variations due to historical and spatial characteristics of a given region.
Keywords: C01; E24; O40; O47; 330; growth regressions; regional analysis; human capital; system GMM; instrumental variables; Regionales Wachstum; Humankapital; Neue Wachstumstheorie; Schätzung; Russland